Evaluation of tribological performance of carbon fibre reinforced epoxy composites loaded with graphite platelets under reciprocating linear motion. (October 2019) - Marat-Mendes, R; Rodrigues, I; Figueiredo-Pina, CG
The objective of this work was to evaluate the effect of graphite platelets used as matrix epoxy polymer reinforcement in the sliding reciprocating wear performance of carbon fibre composites. First, epoxy reinforced composites with different amounts of graphite in weight were produced (0, 7.5, 11.5 and 30 wt %) to ascertain the optimal composition regarding wear resistance. Additionally, carbon fibre reinforced polymer composites were produced, with and without the addition of 7.5 wt% graphite platelets to the polymer matrix, and its wear resistance was also evaluated. The laminated carbon fibre reinforced polymer composites were produced through vacuum assisted hand lay-up method. Reciprocating sphere-on-plate wear tests, using Ø 6 mm spheres of AISI52100 steel as counter-body, were performed during 6 h at room temperature. The tests were carried out using an applied normal load of 4 N, 2 Hz of frequency and 8 mm stroke per cycle. At the end of the tests, the wear losses were estimated through integration of cross-section wear track profiles and the worn surfaces were examined by scanning electron microscopy. The coefficient of friction was accessed during testing. The results showed that the lowest specific wear rate of the polymer composites without carbon fibre was obtained with the insertion of 7.5 wt% of graphite platelets (9.7 × 10 −8 mm 3 /N m) and that increase in the graphite fraction leads to higher material loss as a result of increased fatigue surface. Furthermore, the addition of 7.5 wt% graphite platelets to the epoxy matrix of carbon fibre reinforced polymer composites leads to enhance its wear resistance. The reinforced matrix supports and protects the fibres reducing fibre failure and, consequently, wear.